Temporal Variations of Nutrient Concentration in Leaf and Twigs of Populus deltoides Trees - Singh, Bajrang; Tripathi, K. P. (Indian Forester, 2007)
Monthly variation in nutrient concentrations of leaf and current twigs was observed in 5-yearold Populus deltoides trees planted at Lucknow. Leaves appeared to be more sensitive indicator for all nutrient elements consisting of a relatively high concentration in comparison to twigs. The magnitude of nutrient status was in the order of N > Ca > K > Mg > Na > P> Fe. The levels of N, P and K decreased in the different ways as the season's growth proceeds. In contrast, the concentrations of Ca and Mg increased slightly with fluctuations expressing a polynomial order with the advancement in growing season. Na concentration increased to some extent whereas Fe decreased during the life span of the leaves on the trees from May to December. Nutrient concentration in the twigs remained almost stable except P and Fe, which varied according to foliage concentrations following similar trend during annual cycle. The appropriate time of the sampling was identified in August for the diagnosis of the nutrient status of the stand when all the essential elements remained fairly stable during the season's growth of the plants. Maximum retranslocation was recorded for N (60%), whereas minimum for Mg content (9%) at the termination of growing season.